2001
DOI: 10.1097/00000539-200109000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Plateletpheresis and Autologous Platelet Gel Do Not Reduce Chest Tube Drainage or Allogeneic Blood Transfusion After Reoperative Coronary Artery Bypass Graft

Abstract: Platelet-rich plasma (PRP) is postulated to decrease postoperative mediastinal chest tube drainage (MCTD) and allogeneic blood transfusions (ABT) after surgery with cardiopulmonary bypass. However, recent metaanalysis of the literature reveals that few good quality (therapeutic yield) trials that show a benefit have been published. The potential hemodynamic instability caused by plateletpheresis has not been emphasized. We studied the effect of plateletpheresis on MCTD, ABT, and hemodynamic stability in reoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Three trials (Liu 1998, Stover 2000, Wajon 2001) reported the use of the anti-fibrinolytic agent, epsilon aminocaproic acid (EACA). Liu et al (Liu 1998) administered EACA as a bolus dose of 150mg/kg prior to CPB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three trials (Liu 1998, Stover 2000, Wajon 2001) reported the use of the anti-fibrinolytic agent, epsilon aminocaproic acid (EACA). Liu et al (Liu 1998) administered EACA as a bolus dose of 150mg/kg prior to CPB.…”
Section: Resultsmentioning
confidence: 99%
“…Stover et al (Stover 2000) administered 150mg/kg of EACA as a loading dose over 30 minutes, added 75mg/kg to the CPB circuit priming volume, and maintained a 20mg/kg/hr infusion of EACA throughout the operation. Wajon et al (Wajon 2001) administered 10g of EACA as a bolus dose prior to the commencement of CPB. The use of aprotinin was reported by one trial (Armellin 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[165][166][167][168][169][170][171][172][173][174][175][176][177][178] Additional metaanalyses of RCTs indicate that ANH combined with intraoperative red blood cell recovery compared with intraoperative red blood cell recovery alone is effective in reducing the volume of allogeneic blood transfused (Category A1-B evidence) and is equivocal regarding the number of patients transfused with allogeneic blood (Category A1-E evidence). [165][166][167][168][169][170][171][172][173][174][175][176][177][178] Additional metaanalyses of RCTs indicate that ANH combined with intraoperative red blood cell recovery compared with intraoperative red blood cell recovery alone is effective in reducing the volume of allogeneic blood transfused (Category A1-B evidence) and is equivocal regarding the number of patients transfused with allogeneic blood (Category A1-E evidence).…”
Section: Practice Parametersmentioning
confidence: 99%
“…Αυτή η τεχνική έχει το θεωρητικό πλεονέκτηµα, ότι η βελτίωση του αριθµού και της λειτουργίας των αιµοπεταλίων µπορεί να περιορίσει τη µετεγχειρητική αιµορραγία χωρίς µείωση της ικανότητας µεταφοράς οξυγόνου. Με παραλλαγή αυτής της φυγόκεντρης τεχνικής, είναι πιθανό να αποκτηθούν κλάσµατα που είναι είτε πλούσια είτε πτωχά σε αιµοπετάλια [601,602].Τουλάχιστον 18 µελέτες [602][603][604][605][606][607][608][609][610][611][612][613][614][615][616][617][618][619] και µια µεταανάλυση [620] εκτίµησαν την αποτελεσµατικότητα της πλούσιας σε αιµοπετάλια πλασµαφαίρεσης στον περιορισµό της αιµορραγίας και της µετάγγισης αίµατος µετά από καρδιοχειρουργικές επεµβάσεις. Οι υψηλότερης ποιότητας µελέτες που περιλαµβάνουν τυφλές και τυχαιοποιηµένες µελέτες δεν έδειξαν κανένα όφελος από αυτή την παρέµβαση [611][612][613]618], ενώ άλλες δηµοσιευµένες αναφορές έδειξαν κάποιο όφελος από την πλασµαφαίρεση πλούσια σε αιµοπετάλια.…”
unclassified